2013
DOI: 10.1371/journal.pone.0053179
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Histone Phosphorylation Analysis and Identification of Pf14-3-3 Protein as a Histone H3 Phosphorylation Reader in Malaria Parasites

Abstract: The important role of histone posttranslational modifications, particularly methylation and acetylation, in Plasmodium falciparum gene regulation has been established. However, the role of histone phosphorylation remains understudied. Here, we investigate histone phosphorylation utilizing liquid chromatography and tandem mass spectrometry to analyze histones extracted from asexual blood stages using two improved protocols to enhance preservation of PTMs. Enrichment for phosphopeptides lead to the detection of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 52 publications
0
34
0
3
Order By: Relevance
“…Protein extracts were separated on a 4 to 12% SDS-PAGE gel (Criterion, Bio-Rad) and analyzed by Western blotting using the rabbit antiPfNup116 at 1:500. Horseradish peroxidase (HRP)-conjugated anti-P. falciparum aldolase (ab38905; Abcam) at 1:1,000 and rabbit anti-histone 3 (ab1791; Abcam) at 1:2,000 were used to assess purity of cytoplasmic and nuclear fractions as described previously (21). Secondary antibody detection was done with anti-rabbit-HRP (GE health care) at 1:5,000.…”
Section: Methodsmentioning
confidence: 99%
“…Protein extracts were separated on a 4 to 12% SDS-PAGE gel (Criterion, Bio-Rad) and analyzed by Western blotting using the rabbit antiPfNup116 at 1:500. Horseradish peroxidase (HRP)-conjugated anti-P. falciparum aldolase (ab38905; Abcam) at 1:1,000 and rabbit anti-histone 3 (ab1791; Abcam) at 1:2,000 were used to assess purity of cytoplasmic and nuclear fractions as described previously (21). Secondary antibody detection was done with anti-rabbit-HRP (GE health care) at 1:5,000.…”
Section: Methodsmentioning
confidence: 99%
“…All sequences can be found in EuPathDB (https://eupathdb.org/eupathdb/). most histones, including H3 and H3.3 [52]. These marks are frequently seen in combination with neighboring lysine acetylation (and methylation).…”
Section: H3 Histones: a Multivariant Familymentioning
confidence: 99%
“…Many histone modifications have been mapped across the P. falciparum genome (Bá rtfai et al, 2010;Cui et al, 2007;Gupta et al, 2013;Jiang et al, 2013;Lopez-Rubio et al, 2009;Salcedo-Amaya et al, 2009), and many proteins with predicted histone-binding domains have been identified bioinformatically (Bischoff and Vaquero, 2010). However, very few factors which bind to modified histones have been characterized (Dastidar et al, 2013;Flueck et al, 2009;Pé rez-Toledo et al, 2009).…”
Section: Introductionmentioning
confidence: 99%